2010
DOI: 10.1177/1534735409359772
|View full text |Cite|
|
Sign up to set email alerts
|

A Case of Recurred Hepatocellular Carcinoma Refractory to Doxorubicin After Liver Transplantation Showing Response to Herbal Medicine Product, Rhus verniciflua Stokes Extract

Abstract: There is no established protocol proven to be beneficial for treatment of hepatocellular carcinoma recurrence after liver transplantation. Only a few reports have shown direct treatment by surgery or ablation to be independent predictors of survival for localized recurrence. Moreover, the necessity of immunosuppression to prevent allograft rejection makes many physicians hesitate to administer systemic chemotherapy. This case report documents a case in which the administration of an herbal product, an extract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Our patient had terminal HCC, for which he received palliative care with GCJ and CIK cell-based immunotherapy. The efficacy of these two therapies for HCC has been reported in previous studies (Takayama et al, 2000;Wang et al, 2002;Son et al, 2005;Weng et al, 2008;Hui et al, 2009;Kim et al, 2010;Lee et al, 2015;Chae et al, 2018). RVS extract is an anticancer substance that promotes cancer cell apoptosis, suppresses cancer cell growth, and inhibits angiogenesis (Choi et al, 2012).…”
Section: Adverse Event and Safetymentioning
confidence: 84%
“…Our patient had terminal HCC, for which he received palliative care with GCJ and CIK cell-based immunotherapy. The efficacy of these two therapies for HCC has been reported in previous studies (Takayama et al, 2000;Wang et al, 2002;Son et al, 2005;Weng et al, 2008;Hui et al, 2009;Kim et al, 2010;Lee et al, 2015;Chae et al, 2018). RVS extract is an anticancer substance that promotes cancer cell apoptosis, suppresses cancer cell growth, and inhibits angiogenesis (Choi et al, 2012).…”
Section: Adverse Event and Safetymentioning
confidence: 84%
“…In addition, the anticancer effects of RVS were reported in an in vitro study of various cancer cell lines, including Lewis lung carcinoma, non-small cell lung cancer, human lymphoma, osteosarcoma, and breast cancer cells [ 20 27 28 29 30 ]. Several case studies and clinical studies have reported positive effects of RVS, including tumor size reduction and prolonged survival time, in advanced and metastatic cancer patients [ 16 31 32 33 34 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…RVS is used as a traditional herbal therapy for the treatment of abdominal masses. 14 Its efficacy and safety has been reported for various cancer types, including colon, 15 gastric, 16 hepatobiliary, [17][18][19] renal, 20 pancreatic, 21 and pulmonary. [22][23][24] In these, it has shown improved OS and PFS compared with standard treatments, without significant adverse events.…”
Section: Discussionmentioning
confidence: 99%